International Arbitration as a Pillar of Modern International Law: A Doctrinal and Practical Overview - I Made Suwandana Putra; I Gede Agus Kurniawan (Pena Justisia: Media Komunikasi dan Kajian Hukum, 2025)
International arbitration has emerged as a key mechanism for resolving cross-border disputes in the modern era of international law. As an alternative to national judicial systems, arbitration offers a neutral forum capable of providing legal certainty and protecting the interests of parties, including states, multinational corporations, and individuals. This article examines the role of international arbitration as a pillar of international law, using both doctrinal and practical approaches. From a doctrinal perspective, arbitration is understood through basic principles such as party autonomy, neutrality, finality of awards, and international recognition of arbitration outcomes. From a practical perspective, the discussion covers the effectiveness of international arbitration institutions, such as the International Chamber of Commerce (ICC) and the International Centre for Settlement of Investment Disputes (ICSID), as well as the challenges of practical implementation, including costs, delays, and potential conflicts with domestic legal interests. This article argues that international arbitration is not merely a technical dispute resolution instrument but also a normative instrument that strengthens the legitimacy and stability of the international legal system. Thus, international arbitration can be viewed as a crucial foundation underpinning the development of contemporary international law, as well as a strategic tool for maintaining a balance between national interests and the global order.